Coronary Artery Bypass Grafting Following COVID-19 Infection: Difficulties and Challenges - Joshi, Dharmendra; Sharma, Apurb; K Shrestha, Sanjeet; Sharma, Ranjit; Kumar Deo Bhatta , Yadav; G Rajbanshi, Bijoy (Journal of Nepal Health Research Council, 2022)
The COVID-19 pandemic has raised challenges and dilemmas to perform cardiac surgery in the patients following COVID-19 infection due to lasting adverse impacts of the disease on the lungs. A 74-years-old patient, recently infected by COVID-19, with previous myocardial infarction and multiple percutaneous coronary interventions, in-stent thrombosis to the left anterior descending artery, and low resting saturation, presented with chest pain and underwent urgent coronary artery bypass grafting. His postoperative period remained challenging due to high oxygen requirements. He had otherwise an uneventful recovery and was discharged on domiciliary oxygen, which was weaned off over three months and he continues to do well at six months of follow-up. Keywords: Cardiac surgery; COVID-19; coronary artery bypass surgery; pandemic